2020
DOI: 10.9734/jabb/2020/v23i1130190
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic Activity of Physalis angulata in Streptozotocin Induced Diabetic Wistar Albino Rats

Abstract: Background: Physalis angulata have been extensively used for the management of diabetes in folklore medicine, in Nigeria. Aim: The present study aimed to investigate the antidiabetic effect of aqueous extract of Physalis angulata and its potential mechanisms in streptozotocin-induced diabetic rats. Study Duration: The period of the study was done on 30th September, 2018 at the Department of Biochemistry, Faculty of Basic Medical Sciences, university of Jos, Nigeria. Methodology: Albino rats o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Antidiabetic activity of P. angulata has been studied previously using animal models, such as using whole plant, fruit, and leaves. [22][23][24] The current study added to the literature in which stem extracts were studied. It was revealed that α-glucosidase inhibition activity of INPA and EEPA did not correlate with the phenolic contents of the stem extracts.…”
Section: Discussionmentioning
confidence: 99%
“…Antidiabetic activity of P. angulata has been studied previously using animal models, such as using whole plant, fruit, and leaves. [22][23][24] The current study added to the literature in which stem extracts were studied. It was revealed that α-glucosidase inhibition activity of INPA and EEPA did not correlate with the phenolic contents of the stem extracts.…”
Section: Discussionmentioning
confidence: 99%